Quality Control of Asphalt Mixes Using EM Density Gauge: A Statistical Evaluation of Field Durability - M. Ariel Villanueva-Guzmán; Hugo L. Chávez-García; Elia M. Alonso-Guzmán; Wilfrido Martínez-Molina; Horacio Delgado-Alamilla; Juan F. Mendoza-Sanchez; Marco Antonio Navarrete-Seras; Mauricio Arreola-Sánchez (Applied Sciences)
It is proposed to reduce the statistical uncertainty to make informed decisions in pavement construction, using a non-destructive method to determine the density (p) of asphalt mixtures, a decisive parameter to know the quality of the material studied and the content of voids (air voids), contrasting the results with destructive and physical tests to specimens extracted at the test site. This was carried out in the field with the EM density gauge (electromagnetic), on a 71.2 km long stretch of road. The results of the non-destructive tests were compared with the AASHTO standards. The study was focused on a representative sample of 25.9% of the total population, obtained using intentional stratified statistical sampling; the standard deviation was taken as the decisive value of dispersion in the determination of the p-density of the mixtures. The AASHTO T343 standard establishes that the permissible standard deviation for asphalt mixtures should be 0.050 g/cm3. Supplementary statistical analysis shows that the measurement error of the EM densitometer and the core-sampling method is ±1.8%, and the correlation coefficient within the 95% confidence interval reaches 0.91. The results of the analysis show a convincing trend towards the implementation of non-destructive methods, such as EM density gauge, to guarantee the determination of the quality of asphalt mixtures in the field, reducing the time required to determine the quality of the asphalt mixes. The results of the analysis show a convincing trend towards the implementation of non-destructive methods, such as EM density gauge, to ensure the determination of the quality of asphalt mixtures in the field, reducing the time required to determine the quality of asphalt mixtures.